LIFE HISTORY OF A MAJOR CARP HYBRID ROHU-CATLA - Reddy, P Konda; Varghese, T J (Indian Journal of Fisheries, 2011)
A hybrid, rohu-catla, was produced by crossing male rohu with female catla. The embryonic and larval developments of this hybrid, when compared with those of rohu and catla, showed that the development of the hybrid is normal, without any deformities, and is more or less similar to that of the parental species. The period of incubation in the hybrid was 15 h 42 min., as against 16 h 40 min. in catla and 15 h 30 min. in rohu. The hybrid exhibited intermediate characters in respect of the position of mouth and the nature of lips. The caudal spot in the hybrid was triangular as in catla, but more prominent. The alimentary canal in two-day-old larvae of the hybrid was filled with algae and cladocerans, indicating that feeding had commenced on the second day itself, with yolksac still present.